Seed germination, tree growth and flowering responses of Moringa Oleifera lam. (horseradish tree) to temperature - Robbertse, P.J. (Petrus Johannes), 1932- (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2010.